Bald on Record and Positive Impoliteness in Indonesian Speech Discourse: A Sociolinguistic Study of Prabowo’s Speech at the 2026 National Coordination Meeting on the Environmental Crisis in Bali - Nangi, Sitrin Loda; Erfiani, Ni Made Diana; Awolon, Yohanes Octovianus Lesu; Dewi, Putu Chrisma (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This study examines the use of bald on record and positive impoliteness strategies in President Prabowo Subianto's speech at the National Coordination Meeting (Rakornas) of the Central and Regional Governments held on February 2, 2026. In that forum, the President openly reprimanded the governors and regents of Bali in front of thousands of regional heads from all over Indonesia for their failure to handle the waste crisis, which was deemed to tarnish the national tourism image. This research uses a descriptive qualitative approach by applying Culpeper's (1996; 2011) impoliteness theory framework as the analytical instrument. The data are sourced from official transcripts and video recordings of the speech published by CNN Indonesia (2026) and cross referenced with the official transcript from the Cabinet Secretariat of the Republic of Indonesia. The analysis results show that the bald on record impoliteness strategy dominates through direct criticism without mitigation and explicit commands, while positive impoliteness is present through utterances that publicly belittle the competence of regional officials. Abstrak Studi ini meneliti penggunaan strategi bald on record dan positive impoliteness dalam pidato Presiden Prabowo Subianto pada Rapat Koordinasi Nasional (Rakornas) Pemerintah Pusat dan Daerah yang diadakan pada 2 Februari 2026. Dalam forum tersebut, Presiden secara terbuka menegur para gubernur dan bupati Bali di depan ribuan kepala daerah dari seluruh Indonesia atas kegagalan mereka menangani krisis sampah, yang dianggap mencemari citra pariwisata nasional. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan menerapkan kerangka teori ketidaksopanan Culpeper (1996; 2011) sebagai instrumen analisis. Data diambil dari transkrip resmi dan rekaman video pidato yang diterbitkan oleh CNN Indonesia (2026) dan dicross-referensikan dengan transkrip resmi dari Sekretariat Kabinet Republik Indonesia. Hasil analisis menunjukkan bahwa strategi ketidaksopanan bald on record mendominasi melalui kritik langsung tanpa mitigasi dan perintah eksplisit, sementara ketidaksopanan positif hadir melalui ucapan yang secara publik merendahkan kompetensi pejabat daerah.